Os possíveis efeitos da modalidade de licitação pregão em um órgão representante da administração pública direta: o exército brasileiro - Dias, Luiz Antonio Rodrigues (2003)
E-commerce is an issue involving many aspects related to digital infrastructure utilization in order to support business transaction. There are several ways to exemplify e-commerce, for instance; • The use of vending machines to buy soft drinks, calIing cards and coffee. Automatic telIers to obtain bank balances or to make bill payments. The utilization of c1ients data storage in order to implant a relationship marketing programo • The utilization of nets to interconnect different organizations, inner1y or extemalIy, in order to obtain logistic optimization and to alIow the flux of data required to the organizational management. In spite of the different possibilities in order to adopt e-commerce practices, it should not be expected that these practices could be reproduced, genericalIy, by alI the organizations, because they differ in composition regarding their cultures, structures and other components. Due to the broad character of the e-commerce issue, this paper bring forward a conceptual approach and some of its applications on the are as of marketing, logistic and electronic govemment. It also shows some comments about information systems and communication technologies that support them. It features the differences existent between the organizations using an organizational mo deI which portray the organizations as a set of forces: culture and structure, strategy, people and their roles, and technology, in a dynamic equilibrium among them and inserted in the social, technological, economical, and politic environment, and, for example, it infers possible results that can be expected from the adoption of a bid mo deI, actual or electronic, in the scope ofmilitary organizations ofthe Brazilian Army, regarding the culture, the people and their roles and the technology.